Reseña de Crespo Miguel, Mario (2020): Automatic corpus-based translation of a Spanish FrameNet medical glossary - Sánchez-Saus Laserna, Marta (Pragmalingüística, 2021)
Se trata de una reseña de Crespo Miguel, Mario (2020): Automatic corpus-based translation of a Spanish FrameNet medical glossary.